2016
DOI: 10.1002/lary.25988
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Self-Administered Audiometry Application: An Equivalence Study

Abstract: 2b. Laryngoscope, 126:2382-2388, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 32 publications
1
50
0
4
Order By: Relevance
“…We programmed an integrated suite of software applications that managed remote, unsupervised auditory training and psychophysical testing via a tablet computer [43]. Participants were randomized to the CL or WM group and asked to train for approximately 3.5 hours per week for 8 weeks while wearing their hearing aids (WM group, n = 11, x̃ = 31 total hrs; CL group, n =13, x̃ = 35 total hrs; z = −1.3, P = 0.2, Wilcoxon Rank-Sum).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We programmed an integrated suite of software applications that managed remote, unsupervised auditory training and psychophysical testing via a tablet computer [43]. Participants were randomized to the CL or WM group and asked to train for approximately 3.5 hours per week for 8 weeks while wearing their hearing aids (WM group, n = 11, x̃ = 31 total hrs; CL group, n =13, x̃ = 35 total hrs; z = −1.3, P = 0.2, Wilcoxon Rank-Sum).…”
Section: Resultsmentioning
confidence: 99%
“…Subjects were required to achieve a minimum performance level to assure that basic procedural aspects of the task were learned before the testing blocks began. In previous experiments, we found that home testing using this software interface provided results that were statistically equivalent to manual testing in sound treated rooms [43]. …”
Section: Star Methodsmentioning
confidence: 96%
“…The first category is also called pure-tone audiology which is the main focus of this review study. The feature discrimination threshold test and speech recognition testing are used to obtain supplementary information about pure-tone audiograms [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study provided positive and valuable evidence of using the portable audiometer in the remote area. Whitton, et al [23] compared hearing measurements made at home using self-administered audiometric software against the standard tests with clinical setting. The results showed the statistically equivalent between two approaches.…”
Section: Introductionmentioning
confidence: 99%